Comparative analysis of inflammatory biomarkers for the diagnosis of neonatal sepsis: IL-6, IL-8, SAA, CRP, and PCT - Chen Ying; Yan Aixia; Zhang Li; Hu Xiaoming; Chen Liang; Cui Jun; Fan Zichuan; Li Ying (Open Life Sciences)
Neonatal sepsis (NS) is highly likely to cause death; however, early diagnosis of NS is still a great challenge. This study aimed to determine the diagnostic values of IL-6, IL-8, and serum amyloid A (SAA) in NS patients. C-Reactive protein (CRP), procalcitonin (PCT), interleukin (IL)-6, IL-8, and SAA were detected in 120 infants with NS (60 premature infants [NS-PIs] and 60 term infants [NS-TIs]). Sixty noninfected premature infants and 60 noninfected term infants composed the control group. Receiver operating characteristic (ROC) curves were used to determine the sensitivity and specificity of IL-6, IL-8, and SAA alone and in combination with CRP and PCT. The area under the curve (AUC) was calculated to evaluate the diagnostic value. The clinical characteristics of the subjects were recorded. The expression of CRP, PCT, IL-6, IL-8, and SAA was upregulated in patients with NS compared with control subjects. When the SAA cut-off value was 10.18 mg/L, the greatest AUC for the diagnosis of NS-PIs was for SAA (AUC = 0.833, 95% CI 0.762–0.905, P < 0.001). When the CRP cut-off value was 9.562 mg/L, the smallest AUC for the diagnosis of NS-PIs was for CRP (AUC = 0.776, 95% CI 0.684–0.867, P < 0.001). When the IL-8 cut-off value was 52.03 pg/mL, the greatest AUC for the diagnosis of NS-TIs was for IL-8 (0.821). When the IL-8 cut-off value was 52.03 pg/mL, the greatest AUC for the diagnosis of NS-TIs was for IL-8 (AUC = 0.821, 95% CI 0.745–0.898, P < 0.001). When the CRP cut-off value was 13.18 mg/L, the smallest AUC for the diagnosis of NS-TIs was for CRP (AUC = 0.762, 95% CI 0.667–0.857; P < 0.001). Additionally, according to the AUC value, the best combination was SAA and PCT for NS-PI diagnosis, and the best combination was PCT and IL-6 for NS-TI. In conclusion, compared with PCT and CRP, IL-6, IL-8, and SAA are better diagnostic biomarkers. Moreover, PCT combined with SAA is more suitable for diagnosing NS-PIs, and PCT combined with IL-6 is more suitable for diagnosing NS-TIs.